2015
DOI: 10.1371/journal.pgen.1005754
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulatory Mechanisms Underlying the Spatial and Temporal Regulation of Target-Dependent Gene Expression in Drosophila Neurons

Abstract: Neuronal differentiation often requires target-derived signals from the cells they innervate. These signals typically activate neural subtype-specific genes, but the gene regulatory mechanisms remain largely unknown. Highly restricted expression of the FMRFa neuropeptide in Drosophila Tv4 neurons requires target-derived BMP signaling and a transcription factor code that includes Apterous. Using integrase transgenesis of enhancer reporters, we functionally dissected the Tv4-enhancer of FMRFa within its native c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 107 publications
1
21
0
Order By: Relevance
“…SVP plays an important role in neural development and is involved in the establishment of the central nervous system of D. melanogaster embryos [32], as well as in the proliferation and differentiation of different neuroblasts in later developmental stages [33]. The specific regulatory of SVP indicated that it may repress the induction of the FMRFamide gene prior to target contact [34].…”
Section: Nr2 Subfamilymentioning
confidence: 99%
“…SVP plays an important role in neural development and is involved in the establishment of the central nervous system of D. melanogaster embryos [32], as well as in the proliferation and differentiation of different neuroblasts in later developmental stages [33]. The specific regulatory of SVP indicated that it may repress the induction of the FMRFamide gene prior to target contact [34].…”
Section: Nr2 Subfamilymentioning
confidence: 99%
“…BMP signaling acts via the transcriptional activity of pMad to control neuronal differentiation and synaptic function in Drosophila (9–11,13–15,22,26). BMP signaling plays similarly critical roles throughout vertebrate nervous system development, function and repair (88–94).…”
Section: Discussionmentioning
confidence: 99%
“…A microarray study reported the differential expression of 101 genes in the late larval CNS of controls and wit mutants, which included twit as well as two other confirmed wit -responsive genes, Pburs and FMRFa (25). These additional genes represent candidate BMP effector genes, although they remain unverified as direct targets of pMad/Medea complexes; only in the cases of FMRFamide ( FMRFa ) and trio has such evidence been provided (24,26). Thus, we still know very little about the direct coordinated gene regulatory processes controlled by BMP signaling and pMad/Medea transcriptional activity that underlies neuronal differentiation, plasticity and synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…DIMMED likely acts in a combinatorial manner with other cell-specific transcription factors to determine peptide expression in individual neurons ( Liu et al, 2016 ; Stratmann and Thor, 2017 ). Although DIMMED does not target any single neuropeptide gene ( Hadzic et al, 2015 ), other transcription factors do regulate subtype-specific neuropeptide expression ( Allan et al, 2003 ; Berndt et al, 2015 ). While DIMMED-positive neurons coexpress multiple peptides, not all peptidergic neurons express DIMMED ( Park et al, 2008a ; Diesner et al, 2018b ), and the role of DIMMED in Manduca has not been established.…”
Section: Discussionmentioning
confidence: 99%